Recognizing Leber’s Hereditary Optic Neuropathy to avoid delayed diagnosis and misdiagnosis - La Morgia, Chiara; Cascavilla, Maria Lucia; De Negri, Anna Maria; Romano, Marcello; Canalini, Fabrizio; Rossi, Silvia; Centonze, Diego; Filippi, Massimo (Frontiers in Neurology, 2024)
Leber’s Hereditary Optic Neuropathy (LHON) is a maternally inherited optic nerve disease primarily caused by mutations in mitochondrial DNA (mtDNA). The peak of onset is typically between 15 and 30 years, but variability exists. Misdiagnosis, often as inflammatory optic neuritis, delays treatment, compounded by challenges in timely genetic diagnosis. Given the availability of a specific treatment for LHON, its early diagnosis is imperative to ensure therapeutic appropriateness. This work gives an updated guidance about LHON differential diagnosis to clinicians dealing also with multiple sclerosi and neuromyelitis optica spectrtum disorders-related optic neuritis. LHON diagnosis relies on clinical signs and paraclinical evaluations. Differential diagnosis in the acute phase primarily involves distinguishing inflammatory optic neuropathies, considering clinical clues such as ocular pain, fundus appearance and visual recovery. Imaging analysis obtained with Optical Coherence Tomography (OCT) assists clinicians in early recognition of LHON and help avoiding misdiagnosis. Genetic testing for the three most common LHON mutations is recommended initially, followed by comprehensive mtDNA sequencing if suspicion persists despite negative results. We present and discuss crucial strategies for accurate diagnosis and management of LHON cases.